Optimising the bioreceptivity of porous glass tiles based on colonization by the alga Chlorella vulgaris - Ferrandiz-Mas,V; Bond,T; Zhang,Z; Melchiorri,J; Cheeseman,C (Science of the Total Environment, 2016)
Green façades on buildings can mitigate greenhouse gas emissions. An option to obtain green facades is through the natural colonisation of construction materials. This can be achieved by engineering bioreceptive materials. Bioreceptivity is the susceptibility of a material to be colonized by living organisms. The aim of this research was to develop tiles made by sintering granular waste glass that were optimised for bioreceptivity of organisms capable of photosynthesis. Tiles were produced by pressing recycled soda-lime glass with a controlled particle size distribution and sintering compacted samples at temperatures between 680 and 740 °C. The primary bioreceptivity of the tiles was evaluated by quantifying colonisation by the algae Chlorella vulgaris (C. vulgaris), which was selected as a model photosynthetic micro-organism. Concentrations of C. vulgaris were measured using chlorophyll-a extraction. Relationships between bioreceptivity and the properties of the porous glass tile, including porosity, sorptivity, translucency and pH are reported. Capillary porosity and water sorptivity were the key factors influencing the bioreceptivity of porous glass. Maximum C. vulgaris growth and colonization was obtained for tiles sintered at 700 °C, with 2 of tile. Bioreceptivity was positively 1 correlated with sorptivity and porosity and negatively correlated with light transmittance. The research demonstrates that the microstructure of porous glass, determined by the processing conditions, significantly influences bioreceptivity. Porous glass tiles with high bioreceptivity that are colonised by photosynthetic algae have the potential to form carbon-negative façades for buildings and green infrastructure.